Using Azospirillum Bacteria Isolated from Soil as Bioremediation Agent in Wastewater Contaminated with Cadmium in Iraq - Z. R. Abbas, A. M. Al-Ezee, B. T. Al-Shandah and M. A. Shafeeq (Nature Environment and Pollution Technology, 2024)
Bioremediation is an important technique to remove heavy metals from wastewater. The current research aimed to use Azospirillum bacteria in removing cadmium ions from wastewater. The source of Azospirillum bacteria was the soil of Al-Mishkhab in Al-Najaf province, Iraq (rice fields), while the source of wastewater was taken from the Al-Rustamia wastewater treatment plant, in Baghdad in October 2020. All the experiments were carried out in Soil and Water Research Center, Ministry of Science and Technology. After collecting the soil, the microorganisms were isolated through the Immunomagnetic beads (IMB) process and were incubated on a certain synthesized medium. The concentration of cadmium ion was determined through the Absorption Spectrophotometer (AAS) technique. The Azospirillum colonies were identified and characterized as white colonies while the concentration of cadmium ion ranged from 0.03-1.6 mg/L and applying the microorganism on the wastewater will decrease the concentration up to 99.9% in a process called biosorption. Treatment time was also studied for 24, 48, 72, and 168 hours. The statistical analysis shows that increasing time will enhance the removal of cadmium. Cadmium is one of the heavy metals responsible for soil contamination; bacteria play a crucial role in bioremediation, demonstrating stability in decomposing various compounds and materials. Azospirillum is employed for soil decontamination purposes; increasing incubation time will enhance the removal of the trace element; also further investigate the effect of other factors such as temperature, pH, and the effect of using other microorganisms.